Impact of social media addiction on college students’ academic procrastination: a chain mediated effect of lack of self-control and fear of missing out - Tang, Yuxi; He, Weiguang (Frontiers in Psychology, 2025)
AimSocial media addiction is increasingly receiving global attention, and may exacerbate the mental health problems and academic procrastination in college students. However, the complex relationship and underlying mechanisms between social media addiction and academic procrastination remain unclear. This study aimed to explore how social media addiction affects academic procrastination in college students, and to identify the chain mediating role played by lack of self-control and fear of missing out in this relationship, toward the development of effective interventions for mental health and learning performance.MethodThis cross-sectional survey study recruited 825 college students from 30 provincial-level administrative regions in China through online platforms in June 2025. Four mature scales were used to measure social media addiction, academic procrastination, lack of self-control, and fear of missing out, and Bootstrap method was used to test the mediating effect hypothesis.ResultSocial media addiction, fear of missing out, and lack of self-control positively predicted college students’ academic procrastination. Lack of self-control and fear of missing out not only played separate mediating roles between social media addiction and academic procrastination, but also jointly constituted a chain mediation between them.DiscussionThis study expands the research on the relationship between social media addiction and academic procrastination, providing new insights into reducing the negative impact of social media addiction in the digital age, improving college students’ academic performance, and promoting their mental health.